2006
DOI: 10.1016/j.molcel.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-Dependent Ubiquitination of Cyclin D1 by the SCFFBX4-αB Crystallin Complex

Abstract: Growth factor-dependent accumulation of the cyclin D1 proto-oncogene is balanced by its rapid phosphorylation-dependent proteolysis. Degradation is triggered by threonine 286 phosphorylation, which promotes its ubiquitination by an unknown E3 ligase. We demonstrate that Thr286-phosphorylated cyclin D1 is recognized by a Skp1-Cul1-F box (SCF) ubiquitin ligase where FBX4 and alphaB crystallin govern substrate specificity. Overexpression of FBX4 and alphaB crystallin triggered cyclin D1 ubiquitination and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
336
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(348 citation statements)
references
References 48 publications
7
336
1
4
Order By: Relevance
“…Lack of both αA and αB-crystallin decreases the number of cells that enter the S phase during the cell cycle progression (Bai et al, 2004). Consistent with these studies, the association of αB-crystallin in a complex of FBX has been found to direct the ubiquitination of phosphorylated cyclin D1 during the cell cycle, signifying the importance of αB-crystallin in cell cycle regulation (Lin et al, 2006). Targeting key cell cycle regulatory molecules to the proteasome may be one of the functions of αB-crystallin in the lens epithelial growth control.…”
Section: Ensuring the Successful Completion Of Mitosis And Cytokinesissupporting
confidence: 64%
“…Lack of both αA and αB-crystallin decreases the number of cells that enter the S phase during the cell cycle progression (Bai et al, 2004). Consistent with these studies, the association of αB-crystallin in a complex of FBX has been found to direct the ubiquitination of phosphorylated cyclin D1 during the cell cycle, signifying the importance of αB-crystallin in cell cycle regulation (Lin et al, 2006). Targeting key cell cycle regulatory molecules to the proteasome may be one of the functions of αB-crystallin in the lens epithelial growth control.…”
Section: Ensuring the Successful Completion Of Mitosis And Cytokinesissupporting
confidence: 64%
“…Further studies are, however, warranted to address the possibilities that Erk, IkB kinase-a, and other kinases may also be involved in regulation of cyclin D2 expression through phosphorylation of Thr280. As very recent studies have revealed that ubiquitination of cyclin D1 phosphorylated on Thr286 is mediated by the Skp1-Cul1-F box (SCF) or SCF-like complexes where FBX4 as well as aB crystallin or FBXW8 governs substrate specificity (Lin et al, 2006;Okabe et al, 2006), future studies are also needed to identify the E3 ubiquitin ligase complexes involved in ubiquitination of cyclin D2 phosphorylated on Thr280.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12] One can predict that translation inhibition would consequently lead to downregulation of protein expression, particularly of those proteins having a short half-life such as CDK4, cyclin D and Cdc25. 1,[16][17][18][19] However, we noticed that Cdc25A was degraded upon Roc-A treatment with a much faster rate (with a half-life of less than 15 min) than Cdc25B, CDK4, CDK6 and cyclin D3 (Fig. 1g).…”
Section: Roc-a Suppresses Expression Of Key Proteins Involved In G1-smentioning
confidence: 93%